2018
DOI: 10.7250/bjrbe.2018-13.428
|View full text |Cite
|
Sign up to set email alerts
|

Strength Characteristics of Cement-Rice Husk Ash Stabilised Sand-Clay Mixture Reinforced with Polypropylene Fibers

Abstract: In this paper, stress-strain behaviour of sand-clay mixture stabilised with different cement and rice husk ash percentages, and reinforced with different polypropylene fibre lengths are evaluated. Mixtures are widely used in road construction for soil stabilisation. It is observed that replacing half of the cement percentage (in high cement contents) with rice husk ash will result in a higher unconfined compressive strength. In addition, the presence of 6 mm polypropylene fibres will help to increase the uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The UCS results clearly showed that longer fibre lengths (2.0 cm) have higher increase in strength than shorter fibre lengths (1.0 cm). Many researchers have studied the effect of PE on UCS of soils with similar results (Puppala and Musenda 2007;Naeini and Sadjadi 2008;Ghorbani et al 2018;Oliveira et al 2018;Zukri et al 2017; . Their results revealed that the addition of PE and PP significantly increases the UCS of soil.…”
Section: Unconfined Compressive Strength (Ucs) Testmentioning
confidence: 69%
“…The UCS results clearly showed that longer fibre lengths (2.0 cm) have higher increase in strength than shorter fibre lengths (1.0 cm). Many researchers have studied the effect of PE on UCS of soils with similar results (Puppala and Musenda 2007;Naeini and Sadjadi 2008;Ghorbani et al 2018;Oliveira et al 2018;Zukri et al 2017; . Their results revealed that the addition of PE and PP significantly increases the UCS of soil.…”
Section: Unconfined Compressive Strength (Ucs) Testmentioning
confidence: 69%
“…Finally, it is recommended that an implementation of the concepts derived from this study be applied during the preliminary stages of soil stabilisation for civil construction and related ground improvement applications. A dataset of 392 soils stabilised using cementitious additives'-enriched agro-based pozzolans in various proportions and combinations, compacted and cured for 7, 14 and 28 days were compiled from a very intensive literature search [7,17,21,22,35,44,47,49,50,[53][54][55][56]63,67]. As stated previously, most agro-based pozzolanic materials are composed mainly of alumino-silicates.…”
Section: Introductionmentioning
confidence: 99%
“…e presence of these soils in construction projects should be specifically addressed and treated if necessary due to their undesirable behaviour such as swelling, shrinkage, dispersion, low mechanical strength, and high level of settlement [1][2][3]. To overcome such problems, several approaches are available to treat them, including the use of geosynthetics, piles, electroosmosis techniques, and stabilization [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%